Teachers’ perception on quality assurance in teacher education programmes in Nigerian Universitiies - William Rotimi Okunloye; Issa Nasiru Olokooba; Elizabeth Obiageli Uyanne; Ifeoma P Okafor (Journal of Education and Learning (EduLearn), 2019)
The expectation of the labour market on the quality of graduates produced by Faculties of Education in Nigeria universities has become burning issues that many stakeholders in the education sectorfelt unsatisfactory. It becomes imperative to assessthe challenges of quality assurance in teacher education.This study therefore assessedquality assurance in teacher education in Nigerian universities:  challenges and way forward. A descriptive survey research design was adopted for the study. The population of the study was all university teachers in Faculties of Education in universities in Kwara State, Nigeria. A purposive sampling technique was used to select 240 university teachers. A researcher-design questionnaire was used for data collection for the study. The data collected were analysed using means ranking and standard deviation. The findings of the study showed thatthe provision of teachers with adequate academic and professional formativeexperience for teaching and control of examination system with clear procedures as well as ethics of confidentiality and impartiality are the most needed qualities to be assured in teacher education. Overcrowding that leads to poor classroom management and control; instability of academic calendar and adoption of outdated curriculum and inadequate exposure to practical teaching that ensure professionalism are the major challenges in the teacher education. As way out to the challenges, broadening the curriculum of research methodology to improve the student’s project writing skills and emphasis on the acquisition of knowledge in the teaching subject pedagogy, entrepreneurial studies, and computer literacy for functional education need to be considered. Based on the findings, it was recommended among others that internal quality assessment in teacher education should be strengthened in the Faculties of Education that would allow for improved pre-service teacher quality products in Teacher Education in Nigerian universities.